2004
DOI: 10.1248/bpb.27.702
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Some Medicinal Plants: Prangos ferulacea (Apiaceae), Sedum sempervivoides (Crassulaceae), Malva neglecta (Malvaceae), Cruciata taurica (Rubiaceae), Rosa pimpinellifolia (Rosaceae), Galium verum subsp. verum (Rubiaceae), Urtica dioica (Urticaceae)

Abstract: Reactive oxygen species (ROS) and reactive nitrogen species (RNS) are various forms of activated oxygen and nitrogen, which include free radicals such as superoxide ions (O 2 · Ϫ ), hydroxyl (OH · ) and nitric oxide radicals (NO · ), as well as non-free-radical species such as hydrogen peroxide (H 2 O 2 ) and nitrous acid (HNO 2 ). [1][2][3] In living organisms ROS and RNS can form in different ways. Normal aerobic respiration, stimulated polymorphonuclear leukocytes and macrophages, and peroxisomes appear to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 47 publications
6
48
1
3
Order By: Relevance
“…In comparison with the aforementioned similar studies, flower, petiole and lamina of T. lasiopetalum demonstrate better DPPH scavenging activity. Several studies have also shown a close correlation between polyphenolic and flavonoid contents of extracts and antioxidant activity (Alinezhad et al, 2012;Coruh et al, 2007;Mavi et al, 2004), but our work appears to be the first evidence of antioxidant activity of T. lasiopetalum. Lamina of T. lasiopetalum is widely used in Iranian traditional medicine and there is probably a correlation between its antioxidant ability and its usages in Iranian folk medicine.…”
Section: Resultssupporting
confidence: 69%
“…In comparison with the aforementioned similar studies, flower, petiole and lamina of T. lasiopetalum demonstrate better DPPH scavenging activity. Several studies have also shown a close correlation between polyphenolic and flavonoid contents of extracts and antioxidant activity (Alinezhad et al, 2012;Coruh et al, 2007;Mavi et al, 2004), but our work appears to be the first evidence of antioxidant activity of T. lasiopetalum. Lamina of T. lasiopetalum is widely used in Iranian traditional medicine and there is probably a correlation between its antioxidant ability and its usages in Iranian folk medicine.…”
Section: Resultssupporting
confidence: 69%
“…Para a espécie, já existem relatos sobre as atividades citotóxica , antimicrobianas de seus extratos brutos etanólicos Correa et al, 2005), bem como sobre a presença de triterpenos derivados de friedelanona (Bolzani et al, 1992), do iridóide loganina (Lopes et al, 2004) e do alcaloide indólico vallesiachotamina (Vencato et al, 2005). Além disso, estudos relatam a presença de compostos fenólicos em Palicourea e em outras espécies da família Rubiaceae, como por exemplo, Chomelia obtusa (Barros et al, 2008); Randia hebecarpa (Nazari et al, 2006), Cruciata taurica (Mavi et al, 2004) e Uncaria tomentosa (Ostrakhovich et al, 1997;Pilarski et al, 2006). Com base no conhecido potencial biológico de espécies da família Rubiaceae, os objetivos deste trabalho foram avaliar o potencial antioxidante do extrato bruto e das frações de Palicourea rigida e isolar e identificar seus principais compostos, considerando a possibilidade de verificar se há contribuições destes constituintes na atividade investigada.…”
Section: Introductionunclassified
“…Antioxidant and free radical scavenging properties of U. dioica leaves have been established by several studies (Kanter et al, 2005;Cetinus et al, 2005;Mavi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%